Motivasi Kerja Pada Guru di Sekolah Ditinjau Dari Gender - Naila Amna; Yuda Syahputra (Universitas Cenderawasih, 2022)
This study aims to describe the differences in teacher work motivation in terms of gender in North Sumatra. This research is a comparative study on educators in Sumatra. The sample in this study amounted to 98 teachers (male = 30.6%; female = 69.4%), the teachers who became the research sample were aged 25-58 years with a length of service as educators 1-5 years = 42.8%; 6-10 Years = 8.2%; 11-15 Years = 15.3%; 16-20 Years = 17.3%; > 20 years = 16.3. Sampling using incidental sampling technique (non-probability sampling). Data were collected through two questionnaires, including the work motivation instrument developed from the Vroom (1964)Â theory which consisted of 12 items. The analytical technique used was the Independent Sample t-Test with the help of JASP Version 0.14.1.0. The results show that there are differences in the work motivation of male and female teachers as evidenced by the difference in the mean (1.966), male teachers have higher work motivation than female teachers. However, there is no significant difference in the work motivation of male and female teachers as evidenced by the p-value> 0.05, namely sig = 0.061.